Thermodynamics of Mitochondrial Aspartate Aminotransferases in the Presence of Nanoparticles - Abdulati Salem; Abdusalam Mahmoud; Mahmud Abushhewa; Ramzi Mohsen (Khalij-Libya Journal of Dental and Medical Research, 2023)
Background and objectives. The nanoparticles are extensively used in the fields of biotechnology, the medical biochemistry and nanomedicne for enhancement and improvement drugs targeting in the chemotherapy. This study was conducted firstly, to understand the underlying mechanisms and potential applications of the thermo-inactivation kinetics of mitochondrial aspartate aminotransferase (mAspAT) in the presence of various nanoparticles, specifically TiO2 and Fe3O4, as well as gold nanoparticles (AuNP), secondly, to determine the impacts of nanoparticle concentration on the aggregation process and the influence the conformational stability and thermal behavior of mAspAT. Methods. The mAspAT was isolated from the pig heart, and SDS electrophoresis was used to determine the level of the protein’s purity. A solution of native and modified dextran sulfate nanoparticles was prepared and incubated with mAspAT at various temperatures. The thermo-Inactivation was carried out at different temperatures (45, 50, 55, 60, 65, and 70 °C) and the aggregation of mAspAT was studied at 320 nm using spectrophotometry. The output data was manipulated (Calculations) and analyzed by Software Stadia 6.0. Results. TiO2 and Fe3O4 nanoparticles, both native and dextran sulfate-coated, demonstrated thermoprotective effects on mAspAT at temperatures above 60 °C. The interaction of mAspAT with TiO2 nanoparticles resulted in a decrease in thermoinactivation energy (Ea), indicating increased conformational stability. Therefore, constant thermoinactivation rate (kin) of mAspAT was significantly decreased in the presence of TiO2 nanoparticles. The dextran sulfate modification further enhanced this effect. Conclusion. The study concludes that the interaction of mAspAT with NP results in an increase in the conformation rigidity of the enzyme, which is primarily determined by the nature of NP and can be increased by coating the surface of NP with a polymer dextran sulfate. Also, Gold nanoparticles could potentially be used to increase the stability of mAspAT, preventing it from thermoaggregation.